2021
DOI: 10.3390/nano11030771
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Approach to Untangle Graphene Oxide (GO) Nanosheets Effects on Plants: Plant Growth-Promoting Bacteria Inoculation, Bacterial Survival, and Drought

Abstract: Drought is a limiting factor for agricultural productivity. Climate change threatens to expand the areas of the globe subjected to drought, as well as to increase the severity and duration of water shortage. Plant growth-promoting bacteria (PGPB) are widely studied and applied as biostimulants to increase plant production and to enhance tolerance to abiotic and biotic constraints. Besides PGPB, studies on the potential of nanoparticles to be used as biostimulants are also thriving. However, many studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Graphene oxide (GO), a novel nanomaterial as a soil water retention agent, plays a role in the growth and development of plants ( Shen et al, 2018 ; Xie et al, 2020 ). GO not only increased the drought tolerance of in Zea mays L. and Paeonia ostii ( Zhao et al, 2020 ; Lopes et al, 2021 ), but also enhanced the saline-alkali tolerance of Medicago sativa L. ( Chen et al, 2021 ). In addition, the previous studies showed that the surface morphology and internal structure of Paeonia ostii roots were not obviously different between GO and without GO treatment using SEM and TEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene oxide (GO), a novel nanomaterial as a soil water retention agent, plays a role in the growth and development of plants ( Shen et al, 2018 ; Xie et al, 2020 ). GO not only increased the drought tolerance of in Zea mays L. and Paeonia ostii ( Zhao et al, 2020 ; Lopes et al, 2021 ), but also enhanced the saline-alkali tolerance of Medicago sativa L. ( Chen et al, 2021 ). In addition, the previous studies showed that the surface morphology and internal structure of Paeonia ostii roots were not obviously different between GO and without GO treatment using SEM and TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that GO as an effective soil water retention agent can confer drought stress tolerance to Paeonia ostii without causing toxicity ( Zhao et al, 2020 ). Furthermore, the effects of GO nanosheets were in a drought context, with the osmotic and antioxidant protection conferred by GO nanosheets to drought shoots, leading to higher shoot biomass ( Lopes et al, 2021 ). The findings indicated that GO might increase the drought tolerance of woody plants, but no research on the drought tolerance of soybean plants treated with GO has yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Plant and bacterial samples were extracted in 50 mM potassium phosphate buffer (pH 7.0): 300 μL for bacterial samples < 0.02 g, 600 μL for bacterial samples ≥ 0.02 g, and 600 μL for plant samples. Bacterial samples were sonicated and centrifuged as described in Matos et al (2019) [ 54 ]. Plant samples were homogenized with a pestle and mortar and centrifuged as described in Lopes et al (2021) [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial samples were sonicated and centrifuged as described in Matos et al (2019) [ 54 ]. Plant samples were homogenized with a pestle and mortar and centrifuged as described in Lopes et al (2021) [ 54 ]. The supernatant was collected in a new microtube and used immediately or stored at −80 °C for biochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…E20-8 mitigated adverse impact of water deficit on plants, whereby GO ensured osmotic and antioxidant protection of plants, while Rhizobium sp. E20-8 alleviated negative impact of GO on biochemical processes of plants [ 248 ].…”
Section: Effects Of Gbns On Plantsmentioning
confidence: 99%